STUDY OF FLUID CONTACT ANGLE AND WETTABILITY IN 2D ROCK PORES USING MICROMODEL EXPERIMENT - Rinaldi Arbie, Ahmad
Various industrial applications, such as Enhanced Oil Recovery (EOR) and Carbon Capture Utilization and Storage (CCUS), involve fluid transport in porous media. One of the parameters of effectiveness and efficiency of fluid flow is wettability, represented by the contact angle. This study aims to determine the dynamic contact angle of water and floor cleaner using a rock micromodel. Additionally, it will examine the effects of gravity, pore width, and fluid type on the static contact angle. The study is conducted experimentally by injecting several types of fluids, including water, crude oil, and floor cleaner, into a shale rock micromodel. Fluid flow within the micromodel is observed and recorded using a microscope. The images of the fluid flow are then analyzed to obtain the contact angle and fluid interface behavior. The experimental results reveal that the dynamic contact angles of water and floor cleaner tend to decrease, whereas the flow of oil does not show the formation of a meniscus curvature; instead, the oil adheres to the rock grains due to strong adhesion forces. This indicates that the shale rock exhibits oil-wet wettability. Gravitational forces significantly contribute when the micromodel inclination is at 60°, where the gravity component in the flow direction is 8.49 ????/???? 2 . The pore width also determines the dominance of gravitational and capillary forces; as the pore radius increases, the dominance of gravitational forces also increases.